The enforceability of Wa‘d Mulzim (Binding Promise) from a fiqh perspective: A critical analysis of wa‘d application in sukūk contracts - Md. Sawari, Mohd. Fuad; Nik Abdullah, Nik Azizu; Mat Jubri@Shamsuddin, Mustafa; Abdul Aziz, Akhtarzaitie (IIUM Press, 2018)
Wa‘d (promise) is a concept that is frequently applied in various Islamic financial products. Although this concept has been used widely in Islamic financial products, as a result of the arising Sharī‘ah issues, wa‘d especially wa‘d mulzim (binding promise) in some contemporary practices towards contracts of Islamic financial products, remains a debatable practice among some Sharī‘ah scholars. This research aims to analyse some Sharī‘ah issues pertaining to the application of the wa‘d mulzim in the Islamic finance industry, especially the issue of wa‘d mulzim in sukūk contracts, particularly in partnership-based contracts which are sukūk muḍārabah, and sukūk mushārakah concepts. Two aspects are particularly emphasized. First, wa‘d can be binding in certain conditions, but to legally enforce this concept, there remain disputes and controversial discussions among scholars. Second, this study also discusses the issues of “promise to buy” or “promise to sell” (the asset) at a certain “price” i.e. the price at the same nominal value at which the bond was issued. Hence, this research will try to analyse the opinions of the scholars, certain related fatwas, Sharī‘ah resolutions and guidelines to understand the applicability of the binding promise towards Islamic financial products and ensure that the application of the binding promise is in line with the Sharī‘ah requirements.